Orthoepic-prosodic Foundations of the Kazakh Speech Synthesis - Zhanar, Zhumabayeva; Anar, Fazylzhanova; Zeinep, Bazarbayeva; Aisaule, Amanbayeva; Nazgul, Ospangaziyeva (Forum for Linguistic Studies, 2025)
This article examines the issues related to prosodic and orthoepic norms in Kazakh speech synthesis. To ensure that the synthesizer delivers speech that is both realistic and intelligible, the text must be systematized according to orthoepic standards, with changes in phonemes, vowel reductions, and various sound phenomena described on the basis of linguistic data. The article also outlines the relevance of speech synthesis and the methods employed, while identifying their distinctive features. Furthermore, contemporary speech synthesis programs are discussed, along with their advantages and drawbacks. The article particularly focuses on enhancing speech synthesis by ensuring that narrators read texts in accordance with orthoepic norms and accurately convey prosodic features. The study uses the 11th-grade Kazakh Literature textbook, comprising 62 pages, as its source material. The text was internally segmented into syntagms, and the analysis addressed aspects such as vowel harmony, consonant compatibility, changes between roots and affixes, shifts across rhythmic groups, assimilation, dissimilation, reductions, variations and variants, elision, and other relevant features — all presented in accordance with orthoepic norms. The article analyzes articulatory, formant-based, parametric, and neural models used in the implementation of word synthesis. In order to improve the quality of speech synthesis in the Kazakh language, the study highlights the necessity of expanding abbreviations and numerals, adhering to orthoepic norms, and accurately modeling intonation and rhythmic patterrns. The research findings provide a scientific foundation for developing high-quality speech synthesis based on the phonetic and phonological regularities of the Kazakh language.